Foliage Relationships in Sal (Shorea robusta) - Subba Rao, B. K.; Chaturvedi, A. N. (Indian Forester, 1971)
Several relationships between the foliage weight (oven dry) and other tree dimensions have been developed based on the actual measurementl of various parameters during the clearfelling of 22 years old sal coppice crop. Best relationship was found between the square root of foliage weight and the d.b.h.